History effects in lithium-oxygen batteries : how initial seeding influences the discharge capacity - Rinaldi, Ali (2014)
In laboratory experiments, Li–O2 systems show “sudden death” at capacities far below the theoretical value. Identifying how discharge products limit the total capacity is crucial in Li–O2 system. We investigated the effect of Li2O2 seed layer deposited on carbon cathode under potentiostatic conditions at increasing overpotentials to the subsequent slow discharge at galvanostatic condition. The discharge capacity attainable in the second step is found to vary by more than a factor of 3 depending on the history, i.e., the seed layer. These results provide evidence that the battery history is decisive for the total discharge capacities.